Ras and Rap: are former enemies now friends? - Hariharan, I.K. (Developmental Cell, 2005)
The small GTPase Rap1 was originally thought to function as an antagonist of Ras. A recent paper by provides evidence that Ras and Rap1 function in parallel to activate Raf downstream of the Torso receptor tyrosine kinase in Drosophila.